Identification and Expression Pattern Analysis of Odorant Receptor Family Genes of Tuta absoluta - Zhonglin ZHOU; Gang LIAO; Tingting XIANG; Zhongxiang SUN (Guangdong nongye kexue, 2025)
【Objective】To identify the number and evolutionary relationships of odorant receptor (OR) family genes in the olfactory system of Tuta absoluta, analyze their expression patterns across different developmental stages, and provide insights for pest control strategies.【Method】OR family genes were identified at the genomic level using TBtools and BITACORA software, leveraging the genome sequence of T. absoluta. This was combined with BLAST homology searches and structural domain-based HMMER analyses. The representative sequences of OR family genes of T. absoluta and six other insect species were further compared using MAFFT software, and the phylogenetic analyses were carried out using IQ-TREE software and the expressions of OR genes of T. absoluta were analysed at different developmental stages by using Image GP, and the related genes were verified by qPCR.【Result】A total of 51 OR genes were identified in the T. absoluta genome after homologous gene analysis, structural domain verification, and filtering of incomplete sequences. The coding sequences (CDS) of these genes had an average length of 1 029 bp, with an average of seven exons per gene. Phylogenetic analysis revealed that four genes (TabsOR01, TabsOR28, TabsOR34, and TabsOR38) clustered in a well-defined branch, while the remaining genes were distributed across other branches. Chromosomal localization analysis showed that these 51 TabsOR genes were distributed across 19 different chromosomes, with chromosome 7 harboring the highest number of OR genes (7). Analysis of transcriptome data on the expression of T. absoluta OR genes at different developmental stages showed that OR genes were most highly expressed at the adult stage, followed by the larval stage, with fewer genes expressed in high abundance at the egg stage.【Conclusion】51 OR family genes of T. absoluta were successfully identified, among which 4 genes were clustered in a single branch, and the expression patterns of these OR genes varied in different developmental stages of T. absoluta.